Sosialisasi Undang-Undang Nomor 35 Tahun 2014 Tentang Perlindungan Anak Di Pesantren Putri Hidayatullah Di Kelurahan Batakte Kecamatan Kupang Barat Kabupaten Kupang - Orpa J. Nubatonis; Siti Ramlah Usman; Yossie M.Y. Jacob; Helsina F. Pello (CV. Multi Kreasi Media, 2022)
Child protection is part of the implementation of human rights values. This has the aim of protecting children's rights to live, grow, develop and participate optimally in society.However, in reality the rights of children are often neglected even though there is Law Number 35 of 2014 concerning Child Protection. This is due to the limited knowledge and understanding of the community regarding what to do when children get violence; and there are still many children's rights that are still neglected and protection must still be carried out in the interests of the child's future. So that socialization related to child protection laws is urgently needed to increase knowledge and understanding to the public regarding these laws.